Clinical-surgical characterization of acute cholecystitis in patients treated in the General Surgery Service. Cienfuegos, 2017-2019 - Jorge Luis Estepa Pérez; Tahiluma Santana Pedraza; Jorge Luis Estepa Ramos; José Antonio Feliú Rosa (Medisur, 2023)
Background: acute cholecystitis is an inflammatory disease, characterized by acute changes in the gallbladder wall that can range from edema and congestion to gangrene and perforation. It is a disease with a high incidence in surgical urgency. Objective: to clinically and surgically characterize acute cholecystitis in patients of the General Surgery Service. Methods: a descriptive and prospective study of patients treated for acute cholecystitis in the Surgery Service was carried out from January the 1st, 2017 to December the 31st, 2019. Data were obtained from medical records and operative reports, using a data collection model. The variables age, sex, associated diseases, clinical manifestations, diagnostic confirmation, type of treatment, modality of surgical treatment, evolution, complications, use of antibiotics, place of admission and hospital stay were analyzed. Results: female patients aged 60 years and over predominated; abdominal pain prevailed in most of the patients, accompanied by vomiting and tachycardia; the diagnosis was confirmed through the clinic; surgical treatment predominated, conventional open cholecystectomy was the technique of choice; most progress satisfactorily. Surgical wound sepsis was the most frequent complication. Conclusions: acute cholecystitis is more frequent in the elderly, early diagnosis and timely treatment can reduce the percentage of complications; surgical treatment is the treatment of choice, combined with antibiotic therapy.